Contribution of isolated general practitioner maternity units. Issue 6428 (12th May 1984) - Cavenagh, A J; Phillips, K M; Sheridan, B; Williams, E M
Abstract : A postal survey of isolated general practitioner maternity units in England and Wales showed that just under 4% of deliveries take place in them. Eight per cent of general practitioners are on the staffs, and in 87% of units midwives are integrated with the community midwifery service. Sixty two per cent of units have visiting consultant cover. Fifty seven per cent of patients are booked and delivered in the unit, 28% are booked and deliberately delivered elsewhere, 5% are transferred in the antenatal period, and 10% transferred as emergencies. The perinatal mortality rate for cases booked and delivered in the units is 1.1 per 1000. The number of emergency transfers was appreciably less for those units that were prepared to do their own operations. Thirty five per cent of these units are liable to be cut off in bad weather, and they will continue to fulfil an essential role in the midwifery services.